Marketing Strategy Training and Preparing Financial Reports for SMEs in Pattani Thailand to Form Superior Human Resources - Nuraeni Nuraeni; Hartutik Hartutik; Hasanah Hasanah; M. Irfan Tarmizi; Nor Laila; Adi Mansah (Journal of Applied Sciences and Advanced Technology, 2023)
Over the past 10 years, the world economy has been rocked by various unpredictable circumstances, such as the US and China trade wars, the Covid-19 pandemic, to the war between Russia and Ukraine. The International Monetary Fund (IMF) estimates that global economic losses will reach USD 12.5 trillion or IDR 178,750 trillion and will continue to increase until 2024. In this case, MSMEs are considered to be the sector that was most affected by the economic crisis, threatening the business continuity of many actors. because the decline in people's purchasing power will have an impact on decreasing MSME income. On the other hand, in general, internal MSMEs in almost every country have the same weakness, namely business development that still uses traditional methods. The method used in this Community Service is to collect information/data related to MSME actors and conduct training on Marketing and Accounting. MSMEs are given training on HPP calculations, marketing strategies, preparation of financial reports, and financial recording application training. We feel that the training "Compilation of Financial Statements and Marketing Strategies for MSME Pattani Thailand to Form Superior HR" is a program that can provide benefits for them to be able to develop their potential to become Superior HR and the business they run into a thriving and sustainable business.